2022
DOI: 10.3390/ijerph19127391
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Responses to Climate Change and Anthropogenic Activity in China, 1982 to 2018

Abstract: Climate change and human activities significantly affect vegetation growth in terrestrial ecosystems. Here, data reconstruction was performed to obtain a time series of the normalized difference vegetation index (NDVI) for China (1982–2018) based on Savitzky–Golay filtered GIMMS NDVI3g and MOD13A2 datasets. Combining surface temperature and precipitation observations from more than 2000 meteorological stations in China, Theil–Sen trend analysis, Mann–Kendall significance tests, Pearson correlation analysis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…According to Figure 3, areas where HA contributed more to vegetation changes were mainly distributed in areas showing intensive human factors, such as farmlands and artificial surfaces. Studies by Jin et al [31], Yi et al [41], Li et al [62], Liu et al [70], and Qu et al [71] also showed a similar rule that HA is the main contributor to vegetation change in agricultural areas or urbanization areas. Thus, the findings proved that the residual analysis method using a regression between NDVI and meteorological data, and the use of residuals to indirectly estimate the impact of HA on vegetation changes were suitable.…”
Section: Impact Of Human Activities On the Vegetation Dynamicsmentioning
confidence: 64%
See 1 more Smart Citation
“…According to Figure 3, areas where HA contributed more to vegetation changes were mainly distributed in areas showing intensive human factors, such as farmlands and artificial surfaces. Studies by Jin et al [31], Yi et al [41], Li et al [62], Liu et al [70], and Qu et al [71] also showed a similar rule that HA is the main contributor to vegetation change in agricultural areas or urbanization areas. Thus, the findings proved that the residual analysis method using a regression between NDVI and meteorological data, and the use of residuals to indirectly estimate the impact of HA on vegetation changes were suitable.…”
Section: Impact Of Human Activities On the Vegetation Dynamicsmentioning
confidence: 64%
“…Remote sensing-based normalized difference vegetation index (NDVI) has been extensively used to reflect vegetation dynamics [57][58][59][60][61][62][63]. This study used the Google Earth Engine (GEE) platform to obtain NDVI data of Gannan Prefecture from 2000 to 2020 (https://doi.org/10.5067/MODIS/MOD13A1.006), at spatial and temporal resolutions of 500 m and 16 d, respectively.…”
Section: Datasets 221 Vegetation Remote Sensing Datamentioning
confidence: 99%
“…Variations in land cover are closely related to the human living environment (Gao et al, 2022; Zhang, Jiang, et al, 2022). Vegetation dynamics are mainly influenced by both climate change and human activities (Ge et al, 2021; Li et al, 2022; Zhou et al, 2021). In terms of greening trends, 35% is attributed to climate change, while 65% is associated with human factors (Qiao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of climate change, land use, and habitat loss, global vegetation has changed dramatically over the past 18,000 years (Mottl et al 2021;Li et al 2022). However, the magnitude and patterns of vegetation change are poorly understood at the global scale (Chapin 2003;Mottl et al 2021).…”
Section: Introductionmentioning
confidence: 99%